Enabling the synthesis of homogeneous or Janus hairy nanoparticles through surface photoactivation. Issue 30 (19th July 2018) - Razza, Nicolò; Rizza, Giancarlo; Coulon, Pierre-Eugène; Didier, Lairez; Fadda, Giulia C.; Voit, Brigitte; Synytska, Alla; Grützmacher, Hansjörg; Sangermano, Marco
Abstract : Hairy nanoparticles with either uniform or Janus-like polymer surfaces are generated via light induced-polymerization initiated from the surface. Abstract : Nanoparticles (NPs) homogeneously covered with polymer chains or with chains of two different polymers segregated in distinct domains ("Janus" particles) possess remarkable features. Their unique colloidal properties can be finely tuned by the grafted polymers while the characteristics of the nano-core remain unaffected. Herein, a simple and robust photochemical approach is reported to synthesize, from 50 nm cores, homogeneous and Janus "hairy" nanoparticles with hydrophilic and amphiphilic properties, respectively. This is achieved by using a surface-anchored bis(acyl)phosphane oxide photoinitiator which allows a spatially controlled surface-initiated photopolymerization at room temperature. Homogeneous and Janus hairy nanoparticles dispersed in water have very different interaction behaviours which are directly visualized by in situ liquid cell transmission electron microscopy and confirmed by small angle X-ray scattering from a statistically relevant number of particles.